(Re)Thinking about censorship: art and silencing in the civil-military dictatorship - Neto, Edival Saraiva de Oliveira (Revista do Colóquio, 2024)
This paper aims to understand the censorship and repression of the LGBTQIA+ population during the Brazilian dictatorship, taking as a starting point the artistic manifestations of that period. In the beginning of the text, I will briefly discuss the context of that period. I will then analyze the impact that the 1964 coup had on individuals whose sexuality was seen as deviant, dangerous, and an affront to morality and “good customs”. I will conclude the text by drawing a parallel between the period of the Brazilian civil-military dictatorship and the years of Jair Bolsonaro’s government, when we find, in his speeches, a consonance with the dictatorship period; even encouraging his followers to call for the return of the regime responsible for the death, disappearance, and torture of people.